1999
DOI: 10.1002/(sici)1521-396x(199909)175:1<17::aid-pssa17>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Optical Reflectivity of the Si(111)-(2×1) Surface — The Role of the Electron–Hole Interaction

Abstract: We calculate the optical reflectivity of the Si(111)‐(2×1) surface from first principles. To this end, we first calculate the quasiparticle band structure of the surface within the GW approximation for the electronic self energy. The band structure exhibits two surface bands inside the fundamental bulk band gap. Thereafter the electron–hole interaction is computed for transitions between the relevant bands, the Bethe‐Salpeter equation for coupled electron–hole excitations is solved and the optical response is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
3
3
2
Order By: Relevance
“…As second example, we look at the surface bandstructure of reconstructed Si(111) 2x1 as shown in Figure 6 using the EHT-parameters in Table 28 . Similar to the previous case, the overall shape of the π-and π * -surface bands match qualitatively well with DFT-GW calculations of Rohlfing et al 35 . In Table III we compare our EHT-bandedges and gaps (1st column) at two specific points J and K of the 2D-Brillouin zone with DFT-GW calculations 35,36 and PES/IPES experiments.…”
Section: B Si-surfaces For Different Orientationssupporting
confidence: 87%
See 2 more Smart Citations
“…As second example, we look at the surface bandstructure of reconstructed Si(111) 2x1 as shown in Figure 6 using the EHT-parameters in Table 28 . Similar to the previous case, the overall shape of the π-and π * -surface bands match qualitatively well with DFT-GW calculations of Rohlfing et al 35 . In Table III we compare our EHT-bandedges and gaps (1st column) at two specific points J and K of the 2D-Brillouin zone with DFT-GW calculations 35,36 and PES/IPES experiments.…”
Section: B Si-surfaces For Different Orientationssupporting
confidence: 87%
“…Similar to the previous case, the overall shape of the π-and π * -surface bands match qualitatively well with DFT-GW calculations of Rohlfing et al 35 . In Table III we compare our EHT-bandedges and gaps (1st column) at two specific points J and K of the 2D-Brillouin zone with DFT-GW calculations 35,36 and PES/IPES experiments. The values for the bandedges as well as for the gaps agree quantitatively well among all three calculations, and show also a good agreement with PES/IPES experiments, where the error in the energy resolution is typically 150 − 200 meV depending on temperature and incident energy of the electrons.…”
Section: B Si-surfaces For Different Orientationssupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with earlier work, we observe that the system is semiconducting with two surface state bands spanning the Fermi energy (indicated by the dashed line). These surface state bands are quite dispersive in the direction parallel to the π‐bonded chains (Γ‐J and K‐J′), and more localized perpendicular to the chains (J‐K and J′‐Γ).…”
Section: Resultssupporting
confidence: 91%
“…This variation is related to uncertainty about the magnitude of excitonic effects associated with this surface, with some work suggesting that these effects are small, while other research has indicated that the quasiparticle gap may differ significantly from the optical gap . GW calculations have yielded electronic structures for the Si(111)2 × 1 π‐bonded chain surface in good agreement with experiment. However, such calculations are very computationally demanding.…”
Section: Introductionmentioning
confidence: 97%